2019
DOI: 10.1111/jog.14101
|View full text |Cite
|
Sign up to set email alerts
|

Association between spontaneous ovulation and serum anti‐Müllerian hormone levels in a premature ovarian insufficiency patient after a multimodal treatment for breast cancer

Abstract: The high toxicity of chemotherapy can damage a patient's gonadal function, leading to premature ovarian insufficiency (POI). Here, we report the case of a patient suffering from POI after chemotherapy for breast cancer, who 3 years later ovulated spontaneously and became pregnant. The patient, a 31-year-old infertile women, nulligravida, was diagnosed with breast cancer. The Anti-Müllerian Hormone (AMH) level in her serum was 1.85 ng/mL before multimodal treatment for cancer. She later visited our hospital for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Based on this step, 79 articles were excluded for the following reasons: outcome other than AMH, incomplete data and full text in languages other than English. One study was excluded because it reported the same sample of patients as another [ 33 ] and three studies were excluded because they included fewer than ten patients [ 34 , 35 , 36 , 37 ]. One article was additionally added after hand-searching the references of the included studies [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on this step, 79 articles were excluded for the following reasons: outcome other than AMH, incomplete data and full text in languages other than English. One study was excluded because it reported the same sample of patients as another [ 33 ] and three studies were excluded because they included fewer than ten patients [ 34 , 35 , 36 , 37 ]. One article was additionally added after hand-searching the references of the included studies [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a case report of a patient with premature ovarian insufficiency (POI) exhibited a slight increase in AMH prior to spontaneous ovulation after chemotherapy for breast cancer, and she became pregnant 3 years later. 18 Furthermore, GCs can respond to controlled ovarian hyperstimulation in patients with POI, despite their undetectable AMH levels. 19 This phenomenon suggests that GCs surviving chemotherapy could maintain their function in ovulation.…”
Section: Discussionmentioning
confidence: 99%